Multi-site field trials demonstrate the effectiveness of silicon fertilizer on suppressing dimethylarsenate accumulation and mitigating straighthead disease in rice. (1st January 2023) - Gao, Axiang; Chen, Chuan; Zhang, Huanhuan; Yang, Baoyun; Yu, Yu; Zhang, Wenwen; Zhao, Fang-Jie
Abstract: Rice accumulates both inorganic arsenic (iAs) and organic As species such as dimethylarsenate (DMA). Although DMA is less toxic to humans, it has been shown in hydroponic studies to induce rice straighthead disease, a physiological disorder prevalent in some rice growing regions causing large yield losses. We investigated the effects of different amendments on As species dynamics in soil porewater, accumulation of As species in rice husks and grains, and the incidence of straighthead disease in five field experiments conducted over 2 years at three sites where straighthead disease was observed in previous seasons. The amendments included silicon (Si) fertilizer, micronized zero valent iron (μZVI), sulfate, nitrate, Si-rich biochar, and a mixture of trace and major elements. Straighthead disease was observed in all five experiments. Rice panicles showing the straighthead disease symptoms contained much higher DMA concentrations in husks and grains than normal panicles. Silicon fertilizer was highly effective at decreasing the disease incidence rate and increasing seed setting rate, resulting in 14.9–58.1% increase in grain yield. Silicon fertilizer increased soil porewater iAs and DMA concentrations, but decreased iAs and DMA accumulation in husks and grains, suggesting that Si suppressed the uptake of iAs and DMA by rice plants. Other amendments alleviated straighthead disease to smaller extents than Si fertilizer, with the effect of biochar and the mixture of trace and major elements likely also being attributed to the addition of Si. Results from this field-based study demonstrate that excessive accumulation of DMA is the main cause of rice straighthead disease and Si fertilizer is highly effective at mitigating this disease by suppressing DMA accumulation. Graphical abstract: Image 1 Highlights: Rice straighthead disease occurred in all five field experiments. Dimethylarsenate (DMA) accumulation caused straighthead disease. Silicon suppressed DMA and inorganic As accumulation in rice. Silicon effectively mitigated rice straighthead disease.